CONSTITUTIONAL MORALITY AND ITS ORACLE - Gireesh Kumar J,; Arjun Philip George, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Morality, in simple words, is a code of conduct that may vary from one society to another. Constitution has not defined the term morality anywhere in its articles. The term constitutional morality is an undefined code of conduct. Through its power of interpretation, the Supreme Court is comfortably adding in and deleting conducts that are nowhere mentioned in the constitutional text within the ideal of constitutional morality. While many legal scholars consider constitutional morality to be essential for the proper implementation of the constitution, few others consider it as another weapon of judicial overreach. The courts have time and again used the aid and measure of constitutional conventions, constitutional assembly debates, and precedents to maintain the dynamic character of the constitution to meet the changing wants of society.